The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/tmj.2014.0232
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Utilization of a Novel Smoking Cessation Smartphone App

Abstract: Background: Understanding the characteristics of high and low utilizers of smartphone applications (apps) for smoking cessation would inform development of more engaging and effective apps, yet no studies to date have addressed this critical question. Informed by prior research on predictors of cessation Web site utilization, this study examines the degree to which baseline demographic factors (gender, age, and education), smoking-related factors (smoking level and friends' smoking), and psychological factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 52 publications
5
58
4
Order By: Relevance
“…Other randomised controlled trials comparing two mobile applications using action and commitment theory reported 13% (95% CI,6-22%) quit rate in the intervention (ATC based smart application) versus 8% (95% CI, 3-16%) in control groups (Quit Guide app) 36 . The odds of quitting were 2.9%, (95% CI 0.8-10.3).Two studies measuring 8-weeks cessation rate compared to conventional treatment only and full app adherence post-intervention were two times and four times more likely to achieve cessation, respectively 30,32 . When comparing the smartphone mobile applications with text message smoking cessation support, significantly higher number of quitters were found among the text message support group.…”
Section: Effect Of Intervention On the Outcomementioning
confidence: 97%
See 4 more Smart Citations
“…Other randomised controlled trials comparing two mobile applications using action and commitment theory reported 13% (95% CI,6-22%) quit rate in the intervention (ATC based smart application) versus 8% (95% CI, 3-16%) in control groups (Quit Guide app) 36 . The odds of quitting were 2.9%, (95% CI 0.8-10.3).Two studies measuring 8-weeks cessation rate compared to conventional treatment only and full app adherence post-intervention were two times and four times more likely to achieve cessation, respectively 30,32 . When comparing the smartphone mobile applications with text message smoking cessation support, significantly higher number of quitters were found among the text message support group.…”
Section: Effect Of Intervention On the Outcomementioning
confidence: 97%
“…However, in interventional studies, the average number of the application openings was only 8.5 (SD = 9). Young age, knowledge level, heavier smoking, depression were predictive factors for app utilization studied in three studies 29,32,34 . Audio-visual features were most used aspects of the application followed by quit plan, tracking process and sharing features.…”
Section: App Utilization and Adherencementioning
confidence: 98%
See 3 more Smart Citations